Advanced Study on Pregnancy-Related Low Back Pain Relief after Maximum Static Flexibility Program - Figueira, Helena Andrade; Vale, Rodrigo Gomes de Souza; Rodrigues, Wilma Ferreira Guedes; Figueira, Alan Andrade; Figueira, Joana Andrade; Dantas, Estélio Henrique Martin; Maciel, Renata Franco; Menezes, Ryan Fernando; Carvalho, Beatriz Martins; Lucena, Christiano Lima De; Moura, Alessandra Isabella Santiago Silva; Fonseca, Ana Maria Ribeiro; et al. (Highlights on Medicine and Medical Research Vol. 4, 2021)
Background: Pregnancy-related low back pain (LBP) impacts pregnancy. Pregnancy-related low back pain (LBP) has an impact on daily life for many pregnant women [1] and is characterized by pain in the lower spine responsible for physical and emotional disabilities. Flexibilizing facilitates movements providing posture correction and pain relief. Objective: To analyze effects of a maximum static flexibility program on pregnancy’s LBP. Methods: Clinical prospective randomized controlled trial. Setting: Brazilian Governmental Health Program’s prenatal care. Participants: 40 volunteer of pregnant women, gestational age between 20 and 31 weeks, with/without LBP randomly assigned to experimental group (EG) or control group (CG): EG n = 20 (E1 with LBP and E2 without LBP) and CG n = 20 (C1 with LBP and C2 without LBP). Interventions: EG intervention was sessions of static flexion. CG received conventional medical treatment. Pain intensity was measured by visual analog scale (VAS) of pain. Chi-square, Wilcoxon and the Kruskal-Wallis statistical tests were adopted. Results: Concerning percent variation (?%) E1 presented 56.4% reduction of LBP while E2, C1, C2 increased LBP by 2.9%, 0.1%, 0.5% respectively. Wilcoxon test outcome comparing pre- and post-test of experimental and control groups on pain intensity levels presented significant E1 p < 0.05. Kruskal-Wallis test comparing post-test C1 with E1 with E2 and C2 presented p < 0.05 (C1 post vs. E1 post: p = 0.006; C1 post vs. E2 post: p < 0.0001; C1 post vs. C2 post: p = 0.002), showing significant effect of the experimental treatment. Conclusion: Gains on LBP for EG show that the static flexibilizing exercises reduce and prevent pregnancy-related LBP. The static exercises contributed to reduction or prevention of LBP in pregnant women attended by this Family Health Program. The conventional treatment, based on drug therapy and resting, did not present significant result for LBP in pregnancy.